2012
DOI: 10.17159/2078-516x/2012/v24i1a352
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cricket-related musculoskeletal pain among adolescent cricketers in KwaZulu-Natal

Abstract: Objectives. This study investigated the prevalence and nature of cricket-related musculoskeletal pain among male adolescent cricket players (n=234) residing in the Highway area of Durban over a 12-month period during all the seasons of the year. Methods. Data were collected from five secondary schools. Subjects' participation was dependent on voluntary and parental informed consent. Child assent forms were also provided for the schoolboy cricket players to complete. Participants were required to complete a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 13 publications
4
38
0
Order By: Relevance
“…[3] However, there remains a relative lack of published studies on injury patterns and risk factors in young cricket players, particularly studies reporting injuries with large sample sizes and over more than one season. Seven studies have described injuries in junior cricketers in SA, [4][5][6][7] Australia [8,9] and New Zealand. [10] These studies reported that young cricketers sustain proportionally less overuse injuries than elite players, but were more susceptible to acute traumatic injuries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] However, there remains a relative lack of published studies on injury patterns and risk factors in young cricket players, particularly studies reporting injuries with large sample sizes and over more than one season. Seven studies have described injuries in junior cricketers in SA, [4][5][6][7] Australia [8,9] and New Zealand. [10] These studies reported that young cricketers sustain proportionally less overuse injuries than elite players, but were more susceptible to acute traumatic injuries.…”
mentioning
confidence: 99%
“…[6] Direct physical trauma and overuse were the main causes of this musculoskeletal pain, with the knee being the primary site of injury.…”
mentioning
confidence: 99%
“…The prevalence of cricket-related musculoskeletal pain specific to the various anatomical sites were mostly knee (30%) and lower back (29%), followed by shoulder (17%), ankle (13%) and thigh (11%). 20 In any sport activity Maturation was a significant covariate in anthropometric measures but not in physical performance. Experience and practice are the key factors for improving performance.…”
Section: Discussionmentioning
confidence: 91%
“…Inevitably, injury is potential outcomes of participation hence young athletes are vulnerable to cartilage which is less resistance to repetitive micro injury, apophysis and growth plate's injuries. 1,[3][4][5][6][7] Competitive element intervenes young players' decreased flexibility due to pronounced growth spurt through training harder and longer times which lead to varied physiologic response to exercise hence injuries. 4,[7][8][9] Bowling, batting and fielding are the three unique aspects of the game of cricket which are associated with risks of injury due to its repetitive nature and played often for long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…4,[7][8][9] Bowling, batting and fielding are the three unique aspects of the game of cricket which are associated with risks of injury due to its repetitive nature and played often for long periods of time. 1,10 In cricket, musculoskeletal pain and injuries are very common. They can occur when a player had rapid rotational movements, collisions with other players, struck by a ball or bat, sliding and diving during fielding and over-use injuries; thus physical macro trauma and microtrauma.…”
Section: Introductionmentioning
confidence: 99%